(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Chronic pain is extremely common in developed countries, and people who suffer from illnesses associated with chronic pain frequently have lower levels of vitamin D than those who do not. The use of vitamin D supplements as a potential alternative treatment for patients suffering from chronic pain has been the subject of research. The purpose of this study is to offer an overview of the scientific data and provide some recommendations regarding the use of vitamin D in clinical practise with patients who suffer from chronic pain.